Prevalência da síndrome metabólica em adolescentes utilizando três critérios, com ou sem substituição da glicemia pelo índice Homa-IR e da circunferência da cintura pela relação cintura-altura - Patricia Casagrande Dias de Almeida (2016)
INTRODUCTION: There is great geographical variation in the prevalence of metabolic syndrome (MS), especially in adolescents. One of the causes of this variation is the diversity of criteria used to diagnose the syndrome. OBJECTIVES: (a) To study the prevalence of MS diagnosed according to the criteria established by Cook et al, the International Diabetes Federation (IDF) and a New Criterion, with or without the following modifications: replacement of glucose by HOMA-IR and waist by the waist to-height ratio (WHTR), alone or together; (b) To create a New Criterion based on modifications in Cook and IDF criteria; (c) To evaluate the WHTR, checking their sensitivity to identify obesity and metabolic syndrome. METHODS: A randomized sample of 69 adolescents (10-14 years, 414 girls) from public schools of Metropolitan Region of the Great Victory was studied. Biochemical evaluations, blood pressure, weight and height were obtained according to standardized procedures. The New Criterion (NC) was created using the values of blood glucose and triglycerides as in IDF and values for blood pressure, HDL and waist circumference as in Cook criterion. For the WHTR values 0.480 for girls and for boys 0,487 were considered abnormal. RESULTS: Average age 12.8 ± 1.1 years (girls: 12.9 ± 1.1; boys: 12.8 ± 1.1). The prevalence of MS was 3.9%, 1.5% and 2.6% respectively by the Cook, IDF and NC criteria, with no difference between genders. The replacement of glucose by HOMA increased prevalence with the three criteria (Cook: 10.9%, IDF: 4.3% and NC: 8.6%), the same is true, but to a lesser extent, by replacing the waist by WHTR (Cook: 6.2%; IDF: 2.3% and NC: 4.4%). The double substitution greatly increased prevalence (Cook: 14.5%, IDF: 6.7% and NC: 12.4%). The WHTR showed high sensitivity to identify obesity (95%), but very low sensitivity to identify MS diagnosed by the three criteria (from 6 to 15%). However the WHTR presented good sensitivity to identify adolescents who had at least one sign of the metabolic syndrome (62% to 79%). CONCLUSION: The prevalence of MS in adolescents from public schools in Victoria are similar to observed in other Brazilian regions, with variation according to criterion utilized, and Cook criterion identified more cases. The replacement of glucose by HOMA-IR and waist by WHTR greatly increases the prevalence of the syndrome. The proposed New Criterion identified intermediate number of cases, because the withdrawn of the low value of triglycerides from Cook criterion (which increases the number of cases) and the blood pressure values for adults from IDF criterion (which decreases the number of cases). Although the WHTR showed very low sensitivity to identify MS, it showed good sensitivity to identify adolescents with at least one sign of the syndrome, leading us to admit that WHTR is a good index for screening adolescents to identify cardiometabolic risk.